Child's health in the mirror of numismatics. Report 2. The history of pediatric surgery - O.V. Syniachenko; M.V. Iermolaeva; S.M. Verzilov; K.V. Liventsova; V.V. Gerasymenko; T.R. Polesova (Zaslavsky O.Yu., 2020)
Report 1 presented the definition of numismatics as a historical science, aspects of the study of its components (coins, medals, plaques), the images of common international symbols of pediatrics (Har-pa-Khered, or Harpocrates, a pelican feeding its chicks, and Florentine Infant), it was emphasized the role of prominent scientists and doctors who made an invaluable contribution to the development of pediatrics and they were provided on numismatic materials, their biographies were briefly highlighted. The insufficient modern usage of numismatics facilities in perpetuating the memory of famous pediatricians was emphasized. Report 2 considers the questions of the history of pediatric surgery based on numismatic materials, lists the specialized medical institutions in Argentina, Hungary, Germany, Latvia, Lithuania, Poland, Portugal, Russia, the USA, Uruguay, France, where surgical interventions for sick children are carried out, and scientific forums for children surgeons (congresses, congresses, conferences, symposia) are clarified.